If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b + 2b + -4 = 14 Reorder the terms: -4 + 4b + 2b = 14 Combine like terms: 4b + 2b = 6b -4 + 6b = 14 Solving -4 + 6b = 14 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6b = 14 + 4 Combine like terms: -4 + 4 = 0 0 + 6b = 14 + 4 6b = 14 + 4 Combine like terms: 14 + 4 = 18 6b = 18 Divide each side by '6'. b = 3 Simplifying b = 3
| 4x^2-5x+20-(4x^2+10x)= | | .45x+.1x=x-27 | | ((233987973*x)+(41111687*y))=1 | | 160+50w=30w+500 | | 16t^2-222-24=0 | | 4a=72*42 | | 8+3x=2x+15 | | 4x^3-5x+3x^2+6x^2-5x^3-x= | | 2(10+x)=130 | | 2(5-x)/3=-4 | | 2x^2+2x-3=3+6x | | -5t^2+37t=0 | | 40x+27=5(7x+4)+5x+7 | | 2(x-9)=y-22 | | 10-(x-3)=7(x+8) | | 28B^2+8B=0 | | 5t^2+37t+72=72 | | 2x^3-6x=-4 | | 8y+7x=-75 | | 2x^3-6c=-4 | | 5x+7(7-8x)=8x-4(8x+8) | | x/5x-4=3 | | 2(x-9)=y-26 | | (4n+5)-(-6n+7)=-15n-302 | | (7x+9)(2x-5)=0 | | 16t^2-164t-36=0 | | 10=a+15 | | 5d^2-30d+40=0 | | 7y+3(y-4)=3(y-1)-2 | | 2(5+2x)-4= | | ln(5x+2)=4.5 | | 23*j-9*j^2=-12 |